Serum B cell activating factor and interleukin 10 levels in common variable immunodeficiency: relationship with clinical findings - Mijanovic, Radovan; Andrejevic, Sladjana; Jurisic, Vladimir; Bonaci-Nikolic, Branka (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Common variable immunodeficiency (CVID) is an immunologically and clinically heterogeneous disorder. Disturbed cytokine production is implicated in dysfunctional immune response. The aim of this study was to investigated B-cell activating factor (BAFF) and interleukin (IL)-10 levels in CVID patients. Methods. The study included 28 CVID patients diagnosed and followed during a 20-year period (mean follow-up 14.5 years). Control groups consisted of 4 patients with X-linked agammaglobulinemia (XLA) and 21 healthy subjects. According to clinical characteristics, the CVID patients were divided into four groups which partly overlap: chronic pulmonary diseases (n = 21), splenomegaly (n = 13), autoimmune diseases (n = 9) and patients with recurrent infections despite regular intravenous immunoglobulin (IVIg) substitution (n = 4). The serum levels of BAFF and IL-10 were measured by commercial ELISA. Results. The BAFF levels were found to be higher in all CVID patients compared to the healthy controls (p < 0.01). The most significant differences were observed in the patients with pulmonary diseases and splenomegaly (p < 0.0001). Also, concentrations of IL-10 were higher in all CVID patients in comparison with the XLA patients (p < 0.05) and healthy subjects (p < 0.01). A statistically significant positive correlation (r = 0.86; p < 0.01) was found between the levels of BAFF and IL-10 in the CVID patients with autoimmune diseases. We demonstrated that the CVID patients with chronic pulmonary diseases had higher levels of IL-10, while the CVID patients with recurrent infections had higher BAFF concentrations in comparison to the patients without these features (p < 0.05). Conclusion. In spite of the limited number of patients, this is the first report from Serbia, examining the serum levels of BAFF and IL-10 in the CVID patients. Our study showed significantly increased concentrations of serum BAFF and IL-10 in the patients with CVID compared to the healthy subjects. Further studies are needed to confirm our findings that the BAFF levels are more pronounced in patients with recurrent infections while IL-10 levels are higher in patients with chronic pulmonary diseases.